KERJASAMA INDONESIA-NORWEGIA DALAM KONSERVASI HUTAN INDONESIA MELALUI KERANGKAREDUCING EMISSION FROM DEFORESTATION AND DEGRADATION (REDD+) STUDI KASUS : HUTAN KALIMANTAN TENGAH - Nur Haeda (WANUA : Jurnal Hubungan Internasional, 2017)
This study aims to describe and explain how Indonesia's cooperation with Norway in the conservation of Indonesia's forests through the REDD + Framework is related to the interests of both countries in carrying out this environmental cooperation as well as how the implementation of the REDD + program that both countries have formed for Central Kalimantan's forests. The method used by the writer is descriptive method of analysis, collecting techniques used by the author is literature review. The authors analyzed the data using qualitative analysis techniques supported by quantitative data. The results of this research indicate that the cooperation between Indonesia and Norway certainly has different interests between the two countries. Indonesia itself has the interest to create a good image in the eyes of the international world, this is why Indonesia has a large forest but has various problems, therefore it takes a great commitment also to maintain its forests, Norway itself has a moral obligation to developing countries who has large of forest. The implementation of this REDD + program is the activities undertaken by various parties that mentioned into the Letter Of Intent agreed by Indonesia and Norway.